Coffee intake and gastroesophageal reflux: Relationship with clinical, endoscopic and functional features - Franzoni, Lorella; Crafa, Pellegrino; Franceschi, Marilisa; Rodriguez-Castro, Kryssia Isabel; Brandimarte, Giovanni; Tursi, Antonio; Russo, Michele; Di Mario, Francesco (Acta Biomedica Atenei Parmensis, 2024)
Background and Aim: Coffee consumption seems to play a role in gastroesophageal reflux (GERD). The purpose of this study was to investigate the effect of coffee intake on GERD, in comparison with other clinical conditions.Patients and methods: A total of 449 patients were distributed into three groups. Group 1 (GERD): 239 patients; Group 2 (cholelithiasis): 116 subjects; Group 3 (dyspeptic): 94 patients. In the GERD group symptoms were categorized and related to coffee intake. Serum pepsinogens I and II (PGI and PGII) were measured by immunoassay in group 1 and group 3.Results: All GERD patients showed erosive esophagitis at endoscopy. Cholelithiasis in group 2, was diagnosed by an abdominal ultrasound. Subjects of group 3 fulfilled the Rome III criteria for functional dyspepsia. All subjects filled out a questionnaire about their GI symptoms and coffee intake. Two hundred and ninety-two subjects consumed coffee daily, of which, 148 from group 1, 77 from group 2 and 67 from group 3. Coffee consumption was not different in the three groups. PG I level increased according to daily coffee consumption in GERD and dyspeptic patients. Symptoms of GERD patients worsened as the amount of coffee intake a day increased.Conclusions: Coffee intake was distributed in GERD and the other two control groups, without statistical significance. A relationship was found between coffee and PGI levels, both in GERD and dyspeptic patients. Accordingly, symptoms in GERD patients worsened as the amount of coffee consumed increased, particularly when consumption exceeded 4 cups per day.